An Analysis of Students’ Reading Comprehension through Story Mapping Technique - Andi Kamariah; Syamsinar; Citra Dwi Safitri (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2025)
The overall aim of this study is to analyze the students’ reading comprehension through story mapping technique. This research is provided to explore how story mapping can enhance students’ ability to organize, understand, and retain information from the text. Therefore, the research applied quasi-experimental design was given to the third-semester students in Business English Program, English Department, UNM. In addition to the pre-test and post-test, qualitative data will be collected through student interviews and classroom observations as the instrument to find out the students’ perception. The findings of the research showed that the experimental group, which used the Story Mapping Technique, experienced a significantly greater improvement in reading comprehension compared to the control group, which followed traditional instructional methods. Moreover, the data from interview and observation showed that the students showed positive attitude and perception towards the use of story map in reading activities.